Iraq Crude Oil Exports – February, March, April 2017 - Oil Marketing Company SOMO, Ministry of Oil (Journal of Petroleum Research and Studies, 2018)
Table 1. Iraq Crude Oil Exports – February 2017 Table 2. Iraq Crude Oil Exports – March 2017 Table 3. Iraq Crude Oil Exports – April 2017